An analysis of the execution of digital transformation strategy in a large petrochemical organisation in South Africa - Billett, Leelind Timothy (University of the Witwatersrand, Johannesburg, 2023)
This research paper explored the implementation of digital transformation strategies in a South African petrochemical organization, focusing on the challenges, facilitators, and best practices for successful execution. The study sought to identify common pitfalls in digital transformation success, and solutions to overcome such. The methodology used in this study, which involved qualitative interviews with relevant stakeholders, was deemed appropriate for exploring the subjective experiences and perspectives of the interviewees on strategy execution. A sample population of 12 interview candidates were identified for their expertise and experience in digital transformation and digitisation implementations. The specific population of senior management and digital consultants responsible for interpreting digital transformation strategies was considered relevant and provides a targeted focus for the research objectives. A qualitative analysis tool Atlas. ti (Version 22) was used to analyse the data and derive codes and themes, which formed the basis of the findings and recommendations made in the research paper. The study revealed the importance of strategy execution in the petrochemical industry and identified key barriers and facilitative factors, which included end-user buy-in, resource allocation and executive support factors. The findings of this study reiterated the need for tailored strategies and approaches to implementation, as well as the importance of end-user buy-in and change management. Building on the insights gathered from the research, this paper proposed a framework for successful digital transformation execution, consisting of six interrelated factors: organisational approach, end-user buy-in, tailormade solutions, innovation, experimentation, and change management. The framework could guide organisations in executing their digital transformation goals more efficiently and effectively, taking into account the unique context and challenges faced by the petrochemical industry in South Africa. Overall, this paper highlights the importance of effective strategy execution in digital transformation initiatives, particularly in the petrochemical industry in South Africa. The proposed framework offers a practical guide for organizations seeking to achieve their digital transformation goals while contributing to the broader conversation around digital transformation strategy and execution
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration (MBA) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Execution; Digital transformation; Strategy; Petrochemical organisation; UCTD; SDG-8: Decent work and economic growth